Phenotypic Characteristics and Transcriptome of Cucumber Male Flower Development Under Heat Stress - Chen, Lin; Yun, Maomao; Cao, Zhenqiang; Liang, Zhaojun; Liu, Wenrui; Wang, Min; Yan, Jinqiang; Yang, Songguang; He, Xiaoming; Jiang, Biao; Peng, Qingwu; Lin, Yu’e (Frontiers in Plant Science, 2021)
Cucumber (Cucumis sativus L.) is an important vegetable crop, which is thermophilic not heat-resistant. High temperature stress always results in sterility at reproductive stage. In the present study, we evaluate the male flower developmental changes under normal (CK) and heat stress (HS) condition. After HS, the activity of peroxidase (POD) and superoxide dismutase (SOD), and the contents of malondialdehyde (MDA) were increased. In addition, the pollen fertility was significantly decreased; and abnormal tapetum and microspore were observed by paraffin section. Transcriptome analysis results presented that total of 5828 differentially expressed genes (DEGs) were identified after HS. Among these DEGs, 20 DEGs were found at four stages, including DNA binding transcription factor, glycosyltransferase, and wound-responsive family protein. The GO term of carbohydrate metabolic process was significantly enriched in all anther stages, and many saccharides and starch synthase related genes were significantly different expressed in HS compared CK, such as invertase, sucrose synthase and starch branching enzyme. Furthermore, co-expression network analysis showed a module (midnightblue) strongly consistent with HS, and two hub genes (CsaV3_6G004180 and CsaV3_5G034860) were found with a high degree of connectivity to other genes. Our results provide comprehensive understandings on male flower development in cucumber under HS.